Optimasi Suhu Annealing Marka ISSR Sebagai Langkah Awal Dalam Pengejawantahan Keragaman Genetik Ficus fistulosa dan Ficus variegata - Risqi Aprilianingsih; Baiq Farhatul Wahidah; Muhammad Rifqi Hariri (Gunung Djati Conference Series, 2021)
Ficus is a genus with the largest number of members of the Moraceae tribe which are often found in Indonesia and has a significant role in the tropics as a keystone species. Ficus has a fairly wide distribution with several members of which F. fistulosa and F. variegata can grow in primary forests to urban areas such as Mount Botol, Mount Halimun Salak National Park and Bogor City. Differences in growing locations allow for differences in genetic diversity in plants so that information needs to be explored and disclosed. This study aims to determine the optimum temperature at the annealing stage and to select primers with the best amplicon as the first step to reveal the genetic diversity of F. fistulosa and F. variegata. The molecular marker used is inter simple sequence repeats (ISSR) which is a molecular marker with a very high level of polymorphism and is quite often used to reveal genetic diversity in plants. A total of four samples of F. fistulosa and F. variegata and 10 ISSR primers were used in this study. Modifications in the amplification stage can be done by changing the temperature used based on certain intervals. A good amplicon is influenced by the optimum temperature conditions at the annealing stage when amplification is carried out. Seven ISSR primers were successfully amplified at an annealing temperature of 52 C, while the other two primers were amplified at an annealing temperature of 53 C. The ISSR 5 primer could not be amplified even when the third annealing temperature modification was carried out, so it was not used in the next study. Nine ISSR primers with known optimum temperatures can be used in the study of embodiment of genetic diversity of Ficus spp. in the Bogor City and Mount Botol areas.